Stem Higher Education and Mature-Aged Students: Building a Model for Well-Being and Institutional Support - Šnēbaha, Inga; Jēkabsone, Inga; Ulmane-Ozoliņa, Lāsma; Strazdiņa, Irina; Kulberga, Inta; Budņiks, Leonards; Treija, Rūta; Spjute, Līga; Swenson, Jessica (Journal of Education Culture and Society, 2026)
Aim. As the global demand for Science, Technology, Engineering, and Mathematics (STEM) graduates continues to rise, ensuring the well-being of diverse student groups, including mature-aged students (ages 30 and above), is increasingly recognised as essential for fostering inclusive and sustainable higher education systems. This study explores the well-being dimensions of mature-aged students in STEM programmes through a case study of Riga Technical University (RTU) in Latvia.Methods. Adopting a mixed-methods approach - combining a systematic literature review, a survey, and semi-structured interviews with mature-aged STEM students - the research investigates five key well-being dimensions: academic, financial, physical, psychological resilience, and relational.Results. The findings reveal that mature-aged STEM students’ well-being is shaped by three interrelated factors: academic–relational climate, resource strain and well-being burden, and academic skills and literacies. Faculty engagement, respectful communication, and inclusive learning environments significantly support academic and relational well-being. However, financial and psychological challenges - often linked to work-study-family tensions - require coordinated institutional and policy-level responses.Conclusions. The results underscore the need for flexible academic structures, accessible faculty, and integrated support services. A conceptual model is proposed to guide institutional support, highlighting how systemic interventions across all five well-being dimensions can foster inclusive and sustainable engagement for mature-aged learners in STEM education.